REMOVED: Prediksi Hambatan Kapal Ferry Ro-Ro 750 GT Berbasis Pengujian Hidrodinamika - Ahmad Syafiul Mujahid (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2018)
This article was removed at the request of the authors due to developments in the reported case. Removed article: https://doi.org/10.21070/rem.v3i2.1856 Removal notice: https://doi.org/10.21070/rem.v4i2.3011